Flexible Emotion Regulation: How Situational Demands and Individual Differences Influence the Effectiveness of Regulatory Strategies - Kobylińska, Dorota; Kusev, Petko (Frontiers in Psychology, 2019)
The number of studies and theoretical contributions on emotion regulation has grown rapidly. In this article we describe the concept of flexible emotion regulation. We argue that the effectiveness of specific emotion regulation strategies depends on the interaction of the features of a situation and personality characteristics of the individual regulating his/her emotions. We review a few recent theoretical contributions and studies that have attempted to capture some aspects of the flexibility of emotion regulation rather than distinguish between overly adaptive and maladaptive strategies. Moreover, we discuss potential personality determinants of effectiveness of particular regulatory strategies. We claim that further studies should address the interaction of situational and dispositional factors in shaping the effectiveness of particular emotion regulation strategies. So far, situational and personality determinants have been studied rather separately.